Lymphodepletion – an essential but undervalued part of the chimeric antigen receptor T-cell therapy cycle - Lickefett, Benno; Chu, Lulu; Ortiz-Maldonado, Valentin; Warmuth, Linda; Barba, Pere; Doglio, Matteo; Henderson, David; Hudecek, Michael; Kremer, Andreas; Markman, Janet; Nauerth, Magdalena; Negre, Helene; et al. (Frontiers in Immunology, 2023)
Lymphodepletion (LD) or conditioning is an essential step in the application of currently used autologous and allogeneic chimeric antigen receptor T-cell (CAR-T) therapies as it maximizes engraftment, efficacy and long-term survival of CAR-T cells. Its main modes of action are the depletion and modulation of endogenous lymphocytes, conditioning of the microenvironment for improved CAR-T cell expansion and persistence, and reduction of tumor load. However, most LD regimens provide a broad and fairly unspecific suppression of T-cells as well as other hematopoietic cells, which can also lead to severe side effects, particularly infections. We reviewed 1271 published studies (2011-2023) with regard to current LD strategies for approved anti-CD19 CAR-T products for large B cell lymphoma (LBCL) . Fludarabine (Flu) and cyclophosphamide (Cy) (alone or in combination) were the most commonly used agents. A large number of different schemes and combinations have been reported. In the respective schemes, doses of Flu and Cy (range 75-120mg/m2 and 750-1.500mg/m2) and wash out times (range 2-5 days) differed substantially. Furthermore, combinations with other agents such as bendamustine (benda), busulfan or alemtuzumab (for allogeneic CAR-Ts) were described. This diversity creates a challenge but also an opportunity to investigate the impact of LD on cellular kinetics and clinical outcomes of CAR-T. Only 21 studies explicitly investigated in more detail the influence of LD on safety and efficacy. As Flu and Cy can potentially impact both the in vivo activity and toxicity of CAR-T, a more detailed analysis of LD outcomes will be needed before we are able to fully assess its impact on different T-cell subsets within the CAR-T cell product. The T2EVOLVE consortium propagates a strategic investigation of LD protocols for the development of optimized conditioning regimens.